If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 4(5x + -10) = 38 Reorder the terms: -7x + 4(-10 + 5x) = 38 -7x + (-10 * 4 + 5x * 4) = 38 -7x + (-40 + 20x) = 38 Reorder the terms: -40 + -7x + 20x = 38 Combine like terms: -7x + 20x = 13x -40 + 13x = 38 Solving -40 + 13x = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 13x = 38 + 40 Combine like terms: -40 + 40 = 0 0 + 13x = 38 + 40 13x = 38 + 40 Combine like terms: 38 + 40 = 78 13x = 78 Divide each side by '13'. x = 6 Simplifying x = 6
| d=2(-2d-16)-18 | | 4y-1=2y+1 | | 9x-5=5x+0 | | -5x-1+2x=35 | | 3k+1=7k+11 | | 234*3= | | 2y^2-15y+27=0 | | 5*x=3455 | | 3(2x-5)=6x-9 | | 0.1+36= | | 3x=6-6(x+2)-6 | | 0.3+36= | | 11p-4=1+6p | | -2x+27=-25 | | -2x+9+3x=14 | | 8y-5x=2 | | 31+y=60 | | 15x-(3-(4x+4)-57)=2-x | | 234-80.0= | | 234-8.0= | | 2x-4+3x=5x-16+6x | | 234-0.80= | | 4a+8g=16 | | 21.79+6.89+3.99= | | 6x^2-5x+5=0 | | -2x+8=-7x+10 | | 4x-12(x-2)+38(x-1)=0 | | x^3-3x^2+3x=b | | 7x+14=x(x^2-4) | | (2x-y)i+3=x+12i | | -5+25=m-10 | | -3x+3+2x=-2 |